RISK MATRIX IN ACTION: BUILDING SAFER CITIES THROUGH HOLISTIC URBAN SAFETY MODELS - Wang, Hong Fei (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Urban safety serves as the cornerstone for safeguarding the well-being and assets of urban residents, as well as the fundamental prerequisite for the smooth execution of various productive endeavors. Extensive scholarly efforts, both domestically and internationally, have been dedicated to the exploration of urban safety. Existing studies have primarily delved into the facets of urban safety's essence through the lenses of disaster science, sociology, and economics. Furthermore, they have established evaluation frameworks based on sustainability, "pressure," and "response." Innovations in assessment methodologies, incorporating geographic information systems and game theory, have aimed to enhance our understanding of urban safety. Nonetheless, the practical realization of these research findings necessitates government oversight and execution. The government assumes a pivotal role as the foremost steward of urban safety. This paper, drawing inspiration from prior research, undertakes an objective analysis of various risk factors inherent in urban operations, scrutinized through the lens of government supervision. In doing so, it seeks to construct a scientifically sound and rational assessment system model for urban safety indicators. Furthermore, it quantitatively assesses the risks associated with urban safety. This quantitative approach empowers us to propose targeted risk management strategies, thereby effectively enhancing the safety and security of our cities. This research thus presents a comprehensive and actionable framework for advancing urban safety in the modern urban landscape.